Sustainable removal of N2O by mediated electrocatalytic reduction at ambient temperature electro-scrubbing using electrogenerated Ni(I) electron mediator - Muthuraman, G.; Ramu, A. G.; McAdam, Ewan J.; Moon, Ilshik S. (Elsevier, 2019)
Direct catalysis is generally proposed for nitrous oxide (N2O) abatement but catalysis is expensive, requires high temperatures, and suffers from media fouling, which limits its lifetime. In the present study, an ambient temperature electroscrubbing method was developed, coupling wet-scrubbing with an electrogenerated Ni(I) ([Ni(I)(CN)4]3−) mediator, to enable N2O reduction in a single process stage. The initial studies of 10 ppm N2O absorption into 9 M KOH and an electrolyzed 9 M KOH solution showed no removal. However, 95% N2O removal was identified through the addition of Ni(I) to an electrolyzed 9 M KOH. A change in the oxidation/reduction potential from −850 mV to −650 mV occurred following a decrease in Ni(I) concentration from 4.6 mM to 4.0 mM, which confirmed that N2O removal was mediated by an electrocatalytic reduction (MER) pathway. Online analysis identified the reaction product to be ammonia (NH3). Increasing the feed N2O concentration increased NH3 formation, which suggests that a decrease in electrolyzed solution reactivity induced by the increased N2O load constrained the side reaction with the carrier gas. Importantly, this study outlines a new regenerable method for N2O removal to commodity product NH3 at ambient temperature that fosters process intensification, overcomes the limitations generally observed with catalysis, and permits product transformation to NH3.
Keywords: N2O removal; NH3 formation; Electroscrubbing process; Electrocatalytic reduction